Lossless Data Hiding Using LÂ·SB Method - Kahdum, A. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A loS.sless (reversible) data hiding (embedding) method  inside  an image  (translating medium)  - presented   in  the  present  work  using  L_SB (least  significant  bit). technique  which  enables  us to translate   data  using an  image  (host  image),  using  a  secret  key, to  be  undetectable  without losing  any  data  or  without   changing   the  size  and  the  external   scene (visible  properties) of the image, the hid-ing data is then can  be extracted (without  losing)   by reversing  the encoding  process , knowi11g and  usingthe  same  secret  key. This  method tested  by using  two  images  a:nd byu-sing several   embedding bit  rates     the  result  is  that  the  host  imageundlstinguisbable  from  the  st go  images  ,  then  we  used  (PSNR)  and (MSE)  methods to fined the aifference values between the host image and the stego images.